1989
DOI: 10.1002/pd.1970090307
|View full text |Cite
|
Sign up to set email alerts
|

Meckel–Gruber syndrome: Ultrasonographic diagnosis at 13 weeks' gestational age in an at‐risk case

Abstract: A case of early diagnosis at 13 weeks' gestational age of Meckel-Gruber syndrome by ultrasound is reported in a patient with a 25 per cent recurrence risk. The usefulness of genetic counselling and aimed echographic examination is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 2 publications
0
15
0
1
Order By: Relevance
“…Pardes e t a / (1984) reported a case of Meckel syndrome detected at 21 weeks of gestation by ultrasound, recurring in a family with a past history of this disorder. JEEVAN A. VERNEKAR et al Pachi et al (1989) reported a case of Meckel Gruber syndrome diagnosed by antenatal ultrasonography at 13 weeks gestation in a patient with two previous siblings affected with same disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Pardes e t a / (1984) reported a case of Meckel syndrome detected at 21 weeks of gestation by ultrasound, recurring in a family with a past history of this disorder. JEEVAN A. VERNEKAR et al Pachi et al (1989) reported a case of Meckel Gruber syndrome diagnosed by antenatal ultrasonography at 13 weeks gestation in a patient with two previous siblings affected with same disorder.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, a recent report [9] describes a case of iniencephaly apertus. Another report describes an instance of occipital encephalocele [10],…”
Section: Discussionmentioning
confidence: 99%
“…Zur Absicherung der Diagnose erweist sich die Vermessung des 4. Nach 11 Wochen wird die okzipitale Enzephalozele in der Regel erkannt [35,37]. Ein okzipitaler Defekt war in der Embryonalperiode als Unregelmäûigkeit am Hinterkopf zu sehen [20].…”
Section: Meckel-gruber-syndromunclassified